Transient Pressure Behavior of Complex Fracture Networks in Unconventional Reservoirs. (3rd November 2021) - Feifei, Gou; Chuanxi, Liu; Zongxiao, Ren; Zhan, Qu; Sukai, Wang; Xuejie, Qin; Wenchao, Fang; Ping, Wang; Xinzhu, Wang
Abstract : Unconventional resources have been successfully exploited with technological advancements in horizontal-drilling and multistage hydraulic-fracturing, especially in North America. Due to preexisting natural fractures and the presence of stress isotropy, several complex fracture networks can be generated during fracturing operations in unconventional reservoirs. Using the DVS method, a semianalytical model was created to analyze the transient pressure behavior of a complex fracture network in which hydraulic and natural fractures interconnect with inclined angles. In this model, the complex fracture network can be divided into a proper number of segments. With this approach, we are able to focus on a detailed description of the network properties, such as the complex geometry and varying conductivity of the fracture. The accuracy of the new model was demonstrated by ECLIPSE. Using this method, we defined six flow patterns: linear flow, fracture interference flow, transitional flow, biradial flow, pseudoradial flow, and boundary response flow. A sensitivity analysis was conducted to analyze each of these flow regimes. This work provides a useful tool for reservoir engineers for fracture designing as well as estimating the performance of a complex fracture network.